From waste to thermal regulator: Upcycling preservative-treated wood into multifunctional composite phase change materials for sustainable thermal management - Zhenxin Zhang; Yanan Dong; Lingfeng Kong; Phuocthoi Hoang; Xiaoqi Zhao; Jinzhen Cao (Journal of Cleaner Production, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

Humic acid facilitates microbial manganese oxidation-driven arsenic remediation in soil across a wide temperature range - Weiwei Zhai; Wenjin Zhang; Lingfeng Dong; Yulong Ru; Yao Xu; Zhanfei He; Daoyong Zhang; Xiangliang Pan (Journal of Environmental Management, 2026)

Environmental changes in the Okinawa Trough over the last 88 ka BP: Evidence from high-resolution bulk mineralogy - Lingfeng Luo; Xuguang Feng; Jianjun Zou; Xisheng Fang; Xinru Xue; Ruxi Dou; Baohua Han; Qingchao Wang; Aimei Zhu; Zhi Dong; Gang Yang; Xuefa Shi (Marine Geology, 2026)

Identifying divergence time and paleoclimate change hotspots for better conservation under future climate change - Yuheng Chen; Jonas J. Lembrechts; Yann Hautier; Dongfan Xu; Yao Li; Yuran Dong; Lingfeng Mao (Biological Conservation, 2025)

A novel dual-branch spatial-spectral attention fusion model and method: A case study for the detection of nicotine content in tobacco leaves - Fukang Xing; Rongguang Zhu; Shichang Wang; Lingfeng Meng; Fujia Dong; Songfeng Wang; Jie Ren; Zongxiu Bai; Yapeng Kang (Computers and Electronics in Agriculture, 2025)

Positive contributions of China's protected areas in biodiversity conservation and carbon storage under future climate change - Xuede Dong; Jirui Gong; Frank Yonghong Li; Lingfeng Mao; Weiyuan Zhang; Siqi Zhang; Guisen Yang; Chenyi Yan; Ruijing Wang; Shangpeng Zhang; Tong Wang (Science of The Total Environment, 2025)

Theoretical Model for Load Distribution in Active–Passive Support Systems of Large-Section Tunnels - Zhongxin Xin; Jie Dong; Bo Wang; Lingfeng Sun (Geotechnical and Geological Engineering, 2025)

Adaptive Responses in Byssal Growth and Shedding: Insights from Pteria penguin Under Thread Trimming and Non-Trimming Conditions - Hebert Ely Vasquez; Shangkun Wei; Guoliang Yang; Lingfeng Wang; Peixuan Yu; Mingyue Dong; Chao Yuan; Xing Zheng (Journal of Marine Science and Engineering, 2025)
Bivalves use byssal threads for attachment and locomotion, periodically shedding and regenerating them. In the winged pearl oyster Pteria penguin—known for its strong byssus and its role in the pearl industry—shedding may occur when the byssal stalk reaches a critical size, although the underlying mechanism remains unclear. This study investigated whether artificial manipulation of the byssus (via trimming) could stimulate thread production and promote shedding in adult P. penguin from two size groups. Byssal threads attached to the substrate were trimmed every 3–5 days over a 30-day period and compared to untrimmed controls. Oysters with trimmed byssus produced significantly more threads, with smaller individuals outperforming larger ones in both thread count and byssal stalk diameter. Moreover, small oysters exhibited a higher frequency of complete byssal shedding. These findings suggest that trimming stimulates thread production and accelerates stalk thickening, potentially triggering shedding due to spatial constraints at the attachment site. This response appears to reflect an adaptive mechanism for maintaining effective attachment and may help explain how mechanical or environmental cues influence byssal dynamics. Understanding this process offers new insight into the behavioral and physiological plasticity of P. penguin, with potential applications in pearl oyster management and aquaculture.

Intelligent identification of carbonate components based on deep learning - Yuqing Dong; Chenlin Hu; Jonathan Atuquaye Quaye; Ning Lu; Lingfeng Zhao (Facies, 2025)

Abrupt enhanced Pacific warm water intrusion into the Sea of Okhotsk since the early Holocene - Xuguang Feng; Jianjun Zou; Xuefa Shi; Zhengquan Yao; Zhi Dong; Jiang Dong; Yonghua Wu; Ruxi Dou; Hualong Jin; Aimei Zhu; Xiaojing Wang; Qingchao Wang; et al. (Quaternary Science Reviews, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

Valorization of straw biomass into lignin bio-ink, bacterial cellulose and activated nanocarbon through the trade-off alkali-catalyzed glycerol organosolv biorefinery - Lingfeng Long; Jinkang Chen; Yueqin Cao; Chen Huang; Shoushuai Feng; Hailin Yang; Dong Tian (Chemical Engineering Journal, 2024)

An improved numerical manifold method for crack propagation of concrete gravity dams under seismic loads - Yujie Xu; Yuan Wang; Lingfeng Zhou; Qi Dong (Computers and Geotechnics, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

Contraction of Heat Shock Protein 70 Genes Uncovers Heat Adaptability of Ostrea denselamellosa - Zhen Dong; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2023)

An improved frequency-domain model for the supercritical flow instability analysis in vertical tubes - Lingfeng Bi; Xirong Zhang; Weiteng Li; Tingyu Chen; Xiaocheng Du; Dong Yang (Annals of Nuclear Energy, 2023)

Compound hot extremes exacerbate forest growth decline in dry areas but not in humid areas in the Northern Hemisphere - Hongjun Yang; Wenjing Tao; Qimei Ma; Hanfeng Xu; Lingfeng Chen; Hongjun Dong; Yuchuan Yang; Nicholas G. Smith; Lei Chen (Agricultural and Forest Meteorology, 2023)

Remediation of uranium-contaminated alkaline soil by rational application of phosphorus fertilizers: Effect and mechanism - Lingfeng Dong; Zhanfei He; Jingyi Wu; Keqing Zhang; Daoyong Zhang; Xiangliang Pan (Environmental Research, 2023)

Interaction among soil nutrients, plant diversity and hypogeal fungal trophic guild modifies root-associated fungal diversity in coniferous forests of Chinese Southern Himalayas - Nan Yang; Yan Zhang; Jingji Li; Xiuxiu Li; Honghua Ruan; Parag Bhople; Katharina Keiblinger; Lingfeng Mao; Dong Liu (Plant and Soil, 2022)

Identification of ferroptosis-related signature with potential implications in prognosis and immunotherapy of renal cell carcinoma - Lingfeng Liu; Huan Jin; Mengyuan Dong; Jingwen Tian; Hongsheng Li; Quentin Liu; Yibing Chen; Zhengzhi Zou (Apoptosis, 2022)

Assessment of uranium migration and pollution sources in river sediments of the Ili River Basin using multiply statistical techniques - Lingfeng Dong; Zhanfei He; Fan Zhang; Tao Xu; Jingyi Wu; Kaifang Yan; Xiangliang Pan; Daoyong Zhang (Environmental Science and Pollution Research, 2021)

Grazing by microzooplankton and copepods on the microbial food web in spring in the southern Yellow Sea, China - Yuan Zhao; Yi Dong; Haibo Li; Shiquan Lin; Lingfeng Huang; Tian Xiao; Gerald Gregori; Li Zhao; Wuchang Zhang (Marine Life Science & Technology, 2020)
Assessment of microzooplankton and copepods grazing pressure on picoplankton is a key requirement for resolving the microbial food web efficiency. Although microzooplankton grazing on picoplankton has been extensively studied, the impact of microzooplankton on different groups of picoplankton, i.e., heterotrophic bacteria, Synechococcus and picoeukaryotes have rarely been compared. Furthermore, in the very few existing studies there is no consistent evidence of an enhancing or restraining effect of copepods on picoplankton. More studies are needed to improve our understanding of the influence of microzooplankton and copepod on picoplankton. Dilution incubations and copepod addition incubations were performed during a cruise to the southern Yellow Sea on May 16–29, 2007. The bulk grazing of microzooplankton and the calanoid copepod Calanus sinicus on phytoplankton, flagellates and picoplankton was estimated. Stations were divided into either eutrophic or oligotrophic according to the nutrient and biological parameters. Picoplankton comprised a large part of the diet of microzooplankton in the central oligotrophic area, while phytoplankton was the main food of microzooplankton in the coastal eutrophic area. In the central oligotrophic area, microzooplankton preferred grazing on Synechococcus . After copepod addition, ciliate abundance decreased while Synechococcus abundance increased (382%, 64% and 64% at three experimental stations, respectively), indicating strong grazing pressure of microzooplankton on Synechococcus . Our results suggest that Synechococcus might be an essential carbon source the planktonic food web in the oligotrophic waters of southern Yellow Sea.

Molecular characterization and multiple infections of rotavirus, norovirus, sapovirus, astrovirus and adenovirus in outpatients with sporadic gastroenteritis in Shanghai, China, 2010–2011 - Lijuan Lu; Ran Jia; Huaqing Zhong; Menghua Xu; Liyun Su; Lingfeng Cao; Zuoquan Dong; Niuniu Dong; Jin Xu (Archives of Virology, 2015)

Molecular epidemiology of human calicivirus infections in children with acute diarrhea in Shanghai: a retrospective comparison between inpatients and outpatients treated between 2006 and 2011 - Lijuan Lu; Huaqing Zhong; Menghua Xu; Liyun Su; Lingfeng Cao; Niuniu Dong; Jin Xu (Archives of Virology, 2014)